Differential Proteomic Analysis of Arabidopsis thaliana Genotypes Exhibiting Resistance or Susceptibility to the Insect Herbivore, Plutella xylostella - Collins, Richard M. (Public Library of Science, 2010)

(untitled)
A proteomic study was conducted to investigate physiological factors affecting feeding behaviour by larvae of the insect, Plutella xylostella, on herbivore-susceptible and herbivore-resistant Arabidopsis thaliana. The leaves of 162 recombinant inbred lines (Rils) were screened to detect genotypes upon which Plutella larvae fed least (P. xylostella-resistant) or most (P. xylostella-susceptible). 2D-PAGE revealed significant differences in the proteomes between the identified resistant and susceptible Rils. The proteomic results, together with detection of increased production of hydrogen peroxide in resistant Rils, suggest a correlation between P. xylostella resistance and the production of increased levels of reactive oxygen species (ROS), in particular H(2)O(2), and that this was expressed prior to herbivory. Many of the proteins that were more abundant in the Plutella-resistant Rils are known in other biological systems to be involved in limiting ROS damage. Such proteins included carbonic anhydrases, malate dehydrogenases, glutathione S-transferases, isocitrate dehydrogenase-like protein (R1), and lipoamide dehydrogenase. In addition, patterns of germin-like protein 3 isoforms could also be indicative of higher levels of reactive oxygen species in the resistant Rils. Consistent with the occurrence of greater oxidative stress in the resistant Rils is the observation of greater abundance in susceptible Rils of polypeptides of the photosynthetic oxygen-evolving complex, which are known to be damaged under oxidative stress. The combined results suggest that enhanced production of ROS may be a major pre-existing mechanism of Plutella resistance in Arabidopsis, but definitive corroboration of this requires much further work.